Determination of a Numerical Surge Limit by Means of an Enhanced Greitzer Compressor Model - Tobias Haeckel; Dominik Paul; Sebastian Leichtfuß; Heinz-Peter Schiffer; Werner Eißler (International Journal of Turbomachinery, Propulsion and Power, 2023)
The surge limit of centrifugal compressors is a key parameter in the design process of modern turbochargers. Numerical methods like steady-state simulations are state-of-the-art methods for predicting the performance of the centrifugal compressor. In contrast to that, the determination of the surge limit with any numerical method is still an unsolved challenge. Since the extensive work of Greitzer and many other researchers in this field, it is well-known that surge is a system-dependent phenomenon. In the case of steady-state simulations, the simulation domain is chosen to be as small as possible due to the numerical cost. This simply implies that there is no system information included in the numerical model. Therefore, it is not possible to determine any system-dependent surge limit with today’s applied numerical methods. To overcome this issue, an enhanced Greitzer surge model, which has been developed at Tu Darmstadt, should act as a link between the simulation and the system in which the compressor will be operated. The focus of this paper will rather be on the methodology of determining the surge limit by means of numerical data than on the surge model itself. The methodology will be validated by experimental data of different systems.